Repeat Versus Primary Photorefractive Keratectomy for Treatment of Myopia - Michael Mimouni; Arie Y. Nemet; Dror Ben Ephraim Noyman; Gilad Rabina; Avia Yossefi; Igor Kaiserman (Optics)
Although effective, a portion of photorefractive keratectomy (PRK) patients will suffer residual myopia or relapse to myopic regression. This retrospective, non-randomized, comparative study, aimed to compare the efficacy of primary PRK versus PRK performed as retreatment after previous surgery for myopia. Data regarding the right eye of 220 consecutive myopic patients undergoing repeat or primary PRK in 2013–2017 were extracted. Groups were matched for demographics and preoperative spherical equivalent, sphere, astigmatism, uncorrected and corrected distance visual acuity (UDVA and CDVA). Primary outcomes were an efficacy index (ratio between the postoperative UDVA and the preoperative CDVA), a safety index (ratio between the postoperative and the preoperative CDVA), postoperative UDVA and CDVA, and deviation from target refraction. Primary PRK showed significant superiority in logMAR UDVA (0.01 ± 0.05 versus 0.05 ± 0.10, p = 0.001), logMAR CDVA (0.01 ± 0.05 versus 0.04 ± 0.08, p = 0.01), efficacy index (1.00 ± 0.05 versus 0.97 ± 0.09, p = 0.003) and safety index (1.00 ± 0.06 versus 0.98 ± 0.08, p = 0.04) compared to repeat PRK, but had a significantly higher share of patients with postoperative spherical equivalent (74.5% versus 67.3%) and cylinder (74.5% versus 68.2%) in the range of ±0.5 D. To conclude, enhancement PRK leads to inferior efficacy and safety with greater deviation from target refraction. Adjusted nomograms for repeat PRK may be warranted.